ANALISIS PENGGUNAAN MEDIA INTERNET PADA USAHA MIKRO KECIL MENENGAH (UMKM) JAWA TIMUR UNTUK MENEMBUS PASAR GLOBAL DENGAN METODE O2O - Ayouvi Poerna Wardhanie; Puspita Kartikasari; Sri Hariani Eko Wulandari (Jurnal Bisnis Terapan, 2019)
This study aims to determine how the use of internet media in the Micro, Small, and Medium Enterprises (MSMEs) of East Java to penetrate the Global Market with the O2O Method. MSME is a business activity that plays a major role in the economic development of a nation, but one of the obstacles in the development of MSMEs, especially in Indonesia is the number of business people who are still reluctant to know internet technology, even though with utilizing information technology and internet networks that are more easily accessible and used can help develop the businesses many times. Therefore, the existence of this research is expected to be able to contribute in identifying internet facility and infrastructure ownership in MSMEs, MSME perceptions of the usefulness of information technology in their business, and the interest and mastery of MSME entrepreneurs’ technology in adopting the internet for business development in the global market. The analytical method used is descriptive statistics, with questionnaire instruments. The number of samples in this study are 102 MSMEs in East Java, especially in the fields of trade, hotels, and restaurants. The results of this study are: 87% of MSMEs have not utilized the Marketplace, 79.41% of MSMEs have not utilized E-Commerce, 82.35% of MSMEs have not utilized Crowdsourcing, 78.14% of MSMEs have not marketed their businesses through social media, so it can be concluded that MSMEs at East Java is not ready to penetrate the market global, because of the internet media used so far, most are only used as personal communication tools.